Pengaruh Pelatihan Terhadap Kinerja Karyawan Dengan Kemampuan Kerja Sebagai Variabel Intervening Pada PDAM Kota Malang - Nikmatul Khoiriyah; N Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to test the training on employee performance through the work ability of PDAM Malang City Jl. Sentani Lake Canal No. 100, Madyopuro. This study uses a quantitative method with an explanatory research approach. The number of samples in this study was 76 respondents. The analysis technique uses Path Analysis. The results of the study state that (1) Training has a significant direct effect on employee performance, (2) training has a significant direct effect on work ability, (3) work ability has a significant direct effect on employee performance, (4) training has an indirect effect on employee performance through ability work as an intervening variable. Keywords: Training, Work Ability and Employee Performance